A MICROCOSM BENEATH A DROP OF BLOOD - Mirtalipova Moxizoda Abdusattorovna (Web of Journals Publishing, 2025)
This article analyzes the microcosm - a system of cells and molecules - in human blood from a histological and biophysical point of view. The possibility of identifying such pathological conditions as inflammation, anemia, thrombosis, immune and oncological processes by means of changes in the blood are considered.
Keywords: Blood histology, microcosm, biophysics, pathological processes, inflammation, anemia, thrombosis, immune system, oncological diseases, electroimpedance, spectroscopy, microfluidics.